Phenomenology of baryogenesis from lepton-doublet mixing - Björn Garbrecht; Ignacio Izaguirre (Nuclear Physics B, 2015)
Mixing lepton doublets of the Standard Model can lead to lepton flavour asymmetries in the Early Universe. We present a diagrammatic representation of this recently identified source of CP violation and elaborate in detail on the correlations between the lepton flavours at different temperatures. For a model where two sterile right-handed neutrinos generate the light neutrino masses through the see-saw mechanism, the lower bound on reheat temperatures in accordance with the observed baryon asymmetry turns out to be ≳1.2×109 GeV. With three right-handed neutrinos, substantially smaller values are viable. This requires however a tuning of the Yukawa couplings, such that there are cancellations between the individual contributions to the masses of the light neutrinos.